Antidepresan Non-Psikotropik Kombinasi Ekstrak Air Rimpang Kunyit (Curcuma Longa L.) Dan Ekstrak Aseton Kulit Pisang (Musa Paradisisaca L.) Sebagai Moodbooster Pada Mencit Stres Kronis Ringan - Kamaratih Dwiprasetya, Winda, Nurcahyanti .W.,M.Biomed, Apt (2017)
Turmeric rhizome water extracts alone and banana peels acetone extracts alone has antidepressant activity which have been tested in vivo. This study aimed to combined the Turmeric rhizome water extracts and banana peel acetone extracts to increased the activity of antidepressants. Induction chronic mild stress (CMS) 5 weeks with variety stressors: deprivation mice 12 hours, gave voice predator, cycle inversion dark / light, discolour cage, wet sawdust, reduced sawdust and shaked the cage 15 minutes. Subjects were used 5 groups that given CMC-Na 0,5%, Sertraline 6.5 mg / kg, turmeric extract 560 mg / kg, banana peel extract 200 mg / kg, and combination extract turmeric 560 mg/ kgBB-banana peels 200 mg/ kgBB during 7 days. Antidepressant effect was measured by duration of immobility time (TST and FST), climbing (FST), rearing, grooming, and activity passed central square (OFT) which analyzed using Multivariate-ANOVA and LSD at 95% confidenced level. The combination extract turmeric-banana peels significantly reduced immobility time (p<0.05) in TST (35.66%) and FST (78.95%) and was more potent than single extracts as moodbooster, but didn't significantly reduce duration climbing and didn't significantly increase duration rearing, grooming, and pass central square (locomotor).